Integrative Sozialtheorie?: Esser - Luhmann - Weber - Greshoff, Rainer; Schimank, Uwe; Esser, Hartmut; Luhmann, Niklas; Weber, Max (VS, Verl. für Sozialwiss., 2006)
Mit Beiträgen von: Rainer Greshoff/ Uwe Schimank - Raffael Wittek - Wolfgang L. Schneider - Martin Endreß - Rainer Schützeichel - Thomas Schwietring - Christian Etzrodt - Tilmann Sutter - Martin Abraham/ Bernhard Prosch - Jens Greve - Zenonas Norkus - Dietmar Braun - Wil Martens - Andrea Maurer - Georg Kneer - Andreas Göbel - Thomas Schwinn - Thomas Kron/ Lars Winter - Rainer Greshoff